Qualitative and quantitative variability determined through morphological characterization in amaranth accessions - Ruiz Hernández, Víctor Cuahutémoc; de la O Olán, Micaela; Espitia Rangel, Eduardo; Sangerman-Jarquín, Dora Ma.; Hernández Casillas, Juan Manuel; Schwentesius de Rindermann, Rita (Revista Mexicana de Ciencias Agrícolas, 2018)
The classification within the genus Amaranthus has been quite difficult, mainly because highly segregating characters within the populations have been considered for this. The aim of this study was to morphologically characterize Amaranthus spp., germplasm in order to know the existent qualitative and quantitative variability in the INIFAP’s collection of the genetic resources program (CEVAMEX). During the spring-summer season, 2009, 155 accessions were established in INIFAP’s Mexican Valley Experimental Station in Santa Lucía de Prías, Texcoco, State of Mexico. The morphological characterization was made based on a list of qualitative and quantitative descriptors proposed by Grubben and Van Sloten (1981). All the quantitative studied variables showed high variability, considering the highly significant differences between populations and species. The species A. hypochondriacus was the most frequent with 66.7% of the studied germplasm; other species found were A. cruentus, A. caudatus and A. hybridus. A large variation of colors, sizes and shapes in stem, inf lorescence and leaves within each species was observed for the qualitative traits. The amaranth germplasm available today shows a large morphological diversity, due to a high degree of cross-breeding. There is quite an enormous phenotypic variation between and within the species of Amaranthus genus, which might be used for breeding proposes and also to understand the diversity of this crop in Mexico.
Keywords: Amaranthus spp.; morphological characterization; qualitative and quantitative variability